Lactarane Sesquiterpenes from the European Mushrooms Lactarius aurantiacus, L. subdulcis, and Russula sanguinaria - Malagon Aviles, O. (2014)
The results of the first investigation of secondary metabolites occurring in intact and damaged fruiting bodies of the European mushrooms Lactarius aurantiacus, L. subdulcis, and Russula sanguinaria are reported. The pattern of sesquiterpenes in injured R. sanguinaria is dramatically different from that of Lactarius. The structure of the new furanolactarane 4, isolated from L. aurantiacus, was established on the basis of spectral data.